Social Risk Profile, Planetary Health Diet, and Mortality Risk in Individuals with Metabolic Dysfunction–Associated Steatotic Liver Disease: A Population-Based Study - Xin Li; Hui Fan; Qiuming Yao; Xinhong Gu (Turkish Journal of Gastroenterology, 2026)
Background/Aims: The individual and combined associations of social vulnerability and diet quality with long-term health outcomes in metabolic dysfunction–associated steatotic liver disease (MASLD) remain unclear. The authors aimed to examine the independent and cumulative associations of diet quality and social vulnerability with all-cause and cardiovascular disease (CVD) mortality among US adults with MASLD. Materials and Methods: The authors included 13 518 adults with MASLD from the 1999-2018 National Health and Nutrition Examination Survey, with mortality follow-up through 2019. Diet quality was assessed using the planetary health diet index (PHDI) based on 24-hour dietary recalls. Social vulnerability was evaluated using a composite social risk profile (SRP) score. Cox proportional hazards models were used to derive hazard ratios (HRs) with 95% CIs. Results: Over a median follow-up of 104 months, 1875 deaths, including 643 from CVD, were recorded. Lower PHDI and SRP scores were each associated with significantly higher risks of all-cause and CVD mortality (all P < .05). In the joint analysis, participants with both the lowest PHDI tertile and an SRP score of 0-2 had the highest hazards for all-cause (HR = 3.86, 95% CI: 2.86-5.20) and CVD mortality (HR = 4.94, 95% CI: 2.97-8.20) compared with those with the highest PHDI tertile and an SRP score of 6-8. Subgroup analysis revealed that the associations of SRP score and PHDI with all-cause mortality were stronger among adults younger than 65 years (P for interaction < .001). Conclusion: Poor diet quality and social disadvantage were independently and jointly associated with increased mortality risk among US adults with MASLD, particularly those younger than 65 years. Cite this article as: Li X, Fan H, Yao Q, Gu X. Social risk profile, planetary health diet, and mortality risk in individuals with metabolic dysfunction–associated steatotic liver disease: A population-based study. Turk J Gastroenterol. Published online August 25, 2026. doi: 10.5152/tjg.2026.26301.